2018
DOI: 10.1016/j.bbr.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotide therapy rescues disruptions in organization of exploratory movements associated with Usher syndrome type 1C in mice

Abstract: Usher syndrome, Type 1C (USH1C) is an autosomal recessive inherited disorder in which a mutation in the gene encoding harmonin is associated with multi-sensory deficits (i.e., auditory, vestibular, and visual). USH1C (Usher) mice, engineered with a human USH1C mutation, exhibit these multi-sensory deficits by circling behavior and lack of response to sound. Administration of an antisense oligonucleotide (ASO) therapeutic that corrects expression of the mutated USH1C gene, has been shown to increase harmonin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…For example, the vestibular system might be developmentally sensitive to PAE. Genetic models of vestibular pathology have been observed to spare stop clustering in the open field behavior under light conditions (Donaldson et al, 2018). In contrast, the current study observed that PAE male rats exhibited weaker stop clustering across samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the vestibular system might be developmentally sensitive to PAE. Genetic models of vestibular pathology have been observed to spare stop clustering in the open field behavior under light conditions (Donaldson et al, 2018). In contrast, the current study observed that PAE male rats exhibited weaker stop clustering across samples.…”
Section: Discussionmentioning
confidence: 99%
“…Two minutes after the rat was placed on the open field, four consecutive 5‐min samples of activity were captured for analysis. The 2‐min delay was based on previous work demonstrating that rodents exhibit markers of organized open field behavior including home base establishment (e.g., circling, grooming, and rearing) within 2 min of exposure to a novel environment (Banovetz et al, 2021; Donaldson et al, 2018). Ethovision XT 13 (Noldus) was used to digitize body position in the open field at five frames per second.…”
Section: Methodsmentioning
confidence: 99%
“…An investigation of the organization of exploratory movements in these mice was used to assess spatial organization in both dark and light settings. Typically, mice utilize a combination of environmental as well as self-movement cues as they explore and these activities were found to be disrupted in Usher mice and recovered in Usher mice treated with ASO to correct Ush1c splicing [79].…”
Section: Ush1c/harmoninmentioning
confidence: 99%
“…This partial correction by ASO increases harmonin expression, improves the morphology and structure of stereocilia, leading to a rescue of auditory and vestibular responses in Ush1c mice. This shows that early-treated mice respond better due to an age threshold for effective drug delivery (Lentz et al, 2013;Vijayakumar et al, 2017;Donaldson et al, 2018). Similarly, Ponnath et al (2018) reported restoration of OHC and IHC in Ush1c mice by ASO-29 treatment.…”
Section: Antisense Oligonucleotidesmentioning
confidence: 75%